Artikel Review : Evaluasi pada Sediaan Steril - Safanda Tiara Fitri; Maulidiyah Cholifah; Isna Wulan Mukarromah; Renny Angreyni; Ferdiana Putri Gita Veronika; Dewi Rahmawati; Dzakiya Zhihrotulwida; M. Fithrul Mubarak (An-Najat, 2025)
Sterile preparations are pharmaceutical products that must be free from microorganisms and foreign particles, so they are very important to use in applications that involve direct contact with human body tissue or the circulatory system. The aim of this research is to understand the evaluations that exist on sterile preparations, as well as understanding all the tests carried out on sterile preparations. The method used is the article review method, which sorts thousands of journals into hundreds, tens and up to 5 journals that match the theme. The results obtained are evaluations in sterile preparations, namely organoleptic tests, pH tests, clarity tests, transferred volume tests, homogeneity tests, spreadability tests, adhesion tests, viscosity tests, etc.